Magnetic relaxation measurements in the region of the second magnetization peak in a HgBa2CuO4+delta single crystal - Pissas, M.; Stamopoulos, D.; Moraitakis, E.; Kallias, G.; Niarchos, D.; Charalambous, M. (PHYSICAL REVIEW B, 1999)
The temperature and magnetic-field dependence of activation energy U-o(T,H) for creep has been studied in an HgBa2CuO4+delta single crystal below and above the "fishtail" peak H-sp(T). At constant temperature, U-o(H) increases up to H-sp'(T) and then for H>H-sp'(T) it decreases. H-sp'(T) is located lower than the field H-sp(T) deduced from the hysteresis loops. The decrease of the activation energy is probably indicative of a plastic-type creep of the vortex lattice. We demonstrate that the overall behavior of U-o(T,H) at the second magnetization peak line H-sp(T) in the phase diagram of HgBa2CuO4+delta exhibits similarities with that observed in Bi2Sr2CaCu2O8+delta and YBa2Cu3O6.95 compounds. [S0163-1829(99)04018-7].